(untitled) (Research, Society and Development, 2020)
The prognosis of dental trauma depends on professionals with solid and updated knowledge. The objective was to evaluate the ability of undergraduate dentistry students to develop treatment plans for dental trauma. This cross-sectional, observational, quantitative study had a sample of 242 participants. A clinical case involving avulsion of tooth 11 and complex coronary root fracture of tooth 21 was selected. All data relating to the patient’s exams were added to a clinical record, which was delivered to students in the final year of the undergraduate dentistry course for three years consecutive. The students were instructed to develop a treatment plan for this case. The factors most considered in avulsion treatment plans were: how, when and where the trauma occurred, the patient’s age and systemic condition. Of the students, 39.7% developed an adequate treatment plan, the main mistake being the lack of occlusal adjustment. In addition, 9,9% of students had an adequate treatment plan for coronary artery fracture. The recovery of periodontal biological space and the indication of intraradicular retainers were the main difficulties. It is concluded that undergraduate dentistry students had great difficulty in formulating treatment plans suitable for more severe cases of dentoalveolar trauma involving several specialties.